Analisis Penurunan Tekanan Gas Sulfur Hexafluorida (Sf6) Pada Pemutus Tenaga 150 KV Siemens 3AQ1EG - Rohman; TB. Utami Adi Subekhi; Amri Abdulah; Agus Suprayitno; Prasetyo, Maulana Kukuh (Sekolah Tinggi Teknologi Wastukancana, 2024)
Abstract. The development of technology in the current era is very rapid and has an impact on increasing electrical energy which is a major need for large industries and households. One of the electrical energy delivery equipment in the transmission system is a PMT or High Connection Breaker. This PMT is a mechanical equipment equipped with sulfur hexafluoride (SF6) gas arc extinguishing media. The process of extinguishing the arc occurs due to contact due to work from the movement that causes the contact to cause an arc. This decrease in SF6 gas pressure greatly affects reliability when operating, because the arc extinguishing process is not perfect. This is determined by the age of the equipment and the number of operating breakers. The results showed that SF6 gas which is in accordance with the standard normal pressure of 6.4 bar with an ambient temperature of 34°C can minimize the occurrence of equipment damage because it is able to approach arc pressure with SF6 gas velocity of 58 cm/s.kA, with a contact gap of 3,61224. cm, while the PMT cannot be operated at a pressure of 5.2 bar with an ambient temperature of 34°C because the speed of SF6 gas is 82 cm/s.kA with a contact gap of 5.10696. It is concluded that the higher the pressure affects the speed and distance when extinguishing the arc. several factors that affect the decrease in SF6 gas pressure using the FMEA method based on the highest value of the Risk Priority Number (RPN) of 810. Keywords: fire arc, Breakdown, Voltage breaker, SF6 . gas pressure